Membrane lipid interactions in intestinal ischemia/reperfusion-induced Injury - Slone, Emily Archer; Fleming, Sherry D. (My University, 2015)
Ischemia, lack of blood flow, and reperfusion, return of blood flow, is a common phenomenon affecting millions of Americans each year. Roughly 30,000 Americans per year experience intestinal ischemia-reperfusion (IR), which is associated with a high mortality rate. Previous studies of the intestine established a role for neutrophils, eicosanoids, the complement system and naturally occurring antibodies in IR-induced pathology. Furthermore, data indicate involvement of a lipid or lipid-like moiety in mediating IR-induced damage. It has been proposed that exposure of neo-antigens are recognized by antibodies, triggering action of the complement cascade. While it is evident that the pathophysiology of IR-induced injury is complex and multi-factorial, we focus this review on the involvement of eicosanoids, phospholipids and neo-antigens in the early pathogenesis. Lipid changes occurring in response to IR, neo-antigens exposed and the role of a phospholipid transporter, phospholipid scramblase 1 will be discussed.
Keywords: Ischemia; Reperfusion; Lipids; Neo-antigen